HUBUNGAN PERSEPSI COVID - 19 DENGAN PERILAKU MENCUCI TANGAN PADA KELUARGA BINAAN FK UMSU ANGKATAN 2017 - INDAH WARDANI RANGKUTI; IKA NOPA (LP2MTBM MAKARIOZ, 2021)
COVID-19 is a disease caused by SARS-CoV-2. This virus has entered Indonesia since March 2020. In the past pandemicthe success of government policies to slow the spread of the disease depended on accurate public perceptions. One of theprevention from contracting COVID-19 is by washing hands. To determine the relationship between COVID-19 perceptionand handwashing behavior in FK UMSU assisted families class of 2017. This study is a cross-sectional study. The researchsample was taken using simple random sampling method, amounting to 75 people. The hypothesis test used is the ChiSquare Test. Data were collected based on the COVID-19 Perception questionnaire and a validated hand washing behaviorquestionnaire. The results show that there are 65 respondents who have good perceptions and 68 respondents who havegood behavior. The results of the chi square test obtained p value = 0.001. There is a correlation between the perception ofCOVID-19 with the behavior of washing hands in the FK UMSU assisted families of Class 2017.